A qualitative study of managerial challenges facing small business geographic expansion - Greening, Daniel W.; Barringer, Bruce R.; Macy, Granger (Journal of Business Venturing, 1996)
Geographic expansion is a common growth strategy used by small, entrepreneurial firms. Yet, despite the importance of geographic expansion as a growth strategy, it is a neglected area of small business research. To date, research in the area of small business growth has focused on broad issues, such as the common “obstacles” to firm growth and the relationship between firm growth and firm profitability. Whereas this literature is suggestive, it does not provide specific prescriptive advice to small business managers pursuing geographic expansion as a growth strategy. As a first step in generating prescriptive advice in this area, this study examined the managerial challenges that faced one small firm during the early stages of its efforts to expand geographically. The subject organization, referred to as the Local Advertising Company (LAC), operated in a single location from 1968 to 1990. As a means to initiate firm growth, the owners of the company opened eight new locations in 1991 and eight more in 1992. However, problems ensued. This study used a qualitative research methodology to conduct an assessment of the managerial challenges facing the LAC during its geographic expansion effort. Seventeen key employees of LAC were interviewed for the study. The qualitative case study methodology used provided an opportunity to gather in-depth information from informants regarding their individual assessment of the managerial challenges encountered by LAC during its geographic expansion. Collectively, the respondents identified a number of specific management issues that became problematic during LAC's geographic expansion effort. Through a content analysis technique, these issues were organized into 15 thematic categories including training, recruitment and selection, the relationship between the field staff and the original owners, and 12 others. Each of these categories represents the separate managerial challenges faced by the company during its geographic expansion. The study provides a descriptive analysis of each of the 15 categories of managerial challenges that emerged. The research results suggest that the successful management of a geographic expansion growth strategy requires managers to deal with a unique set of issues. For example, the training of new employees may become problematic when the most experienced personnel in the firm reside in the home office and the new trainees are located in widely dispersed geographic locations. In addition, the results of the study provide an extension to both practical and theoretical knowledge in three distinct areas: planning for growth, managing growth, and the reasons for growth. First, the results of the study support the importance of planning for growth, but suggest that planning must be complemented by learning and a willingness to evolve one's plan as growth progresses. In terms of the management of growth, the case shows that running a small business and growing a small business do not include the same skill set. The owners of LAC had been quite successful managing their single location for 22 years. However, this ability to run a business did not complement the need to anticipate start-up problems in new, remote sites, which is inherent in a strategy of geographic expansion. In addition, the case demonstrated that the management of growth requires a cognizance on the part of the original owners of a firm to delegate control. Finally, with regard to the reasons for growth, researchers generally characterize firm growth as being motivated by either economic (e.g., economies of scale) or emotional reasons (e.g., employing family members). The owners of LAC initiated firm growth for the purpose of wealth creation to fund their retirements. This illustrates that firm growth can be motivated by a combination of both economic (e.g., wealth creation) and personal (e.g., retirement security) reasons.